2018
DOI: 10.1177/2325967118783982
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Shoulder Labral Injury in Collegiate Football Players at the National Football League Scouting Combine

Abstract: Background:Labral tears confirmed by magnetic resonance imaging (MRI) are a relatively common injury among collegiate athletes and can influence a player’s ability to compete at the professional level.Purpose:To determine the prevalence of MRI-confirmed shoulder labral injuries in collegiate football players entering the National Football League (NFL) Combine and to further describe these injuries by tear location, player position, history of surgical intervention, and associated concomitant shoulder injuries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…Unlike the negative effect of concomitant injures with anterior labral injuries, 20 concomitant injuries did not significantly affect any metric when combined with posterior labral tears, perhaps suggesting that the labral tear is the most limiting factor in posterior instability. This may be because of the nature of the injury, with anterior instability generally occurring in a more acute, traumatic mechanical fashion and posterior instability occurring with repetitive, chronic microtrauma in which significant concomitant injuries are less likely to be present.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Unlike the negative effect of concomitant injures with anterior labral injuries, 20 concomitant injuries did not significantly affect any metric when combined with posterior labral tears, perhaps suggesting that the labral tear is the most limiting factor in posterior instability. This may be because of the nature of the injury, with anterior instability generally occurring in a more acute, traumatic mechanical fashion and posterior instability occurring with repetitive, chronic microtrauma in which significant concomitant injuries are less likely to be present.…”
Section: Discussionmentioning
confidence: 79%
“…This is important, considering that linemen have a significantly higher risk for labral tears in at least 1 shoulder. 21 Mair et al 19 hypothesized that contact athletes who engage their opponents with their arms in front of the body, as linemen typically do, were more susceptible to this injury because of the compressive force and shearing force that result from repeated posteriorly directed impact. With modern blocking and block-shedding techniques, the posterior capsule is subject to repetitive microtrauma, which can lead to attenuation of the labrum and laxity of the posterior capsule, resulting in posterior instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this pathology in cases of glenohumeral instability involve the humeral head being displaced anteriorly from the glenoid labrum; this theoretically reinforces the rationale for the high frequencies of bony and chondral pathologies in collision athletes such as rugby players. Although the literature widely reports that American football athletes have a similarly increased risk of glenoid labral tears (among other pathologies) secondary to collisions, [19][20][21] Knapik et al 22 reported that not only unilateral tears are commonplace in this cohort but so too are recurrent and bilateral tears on MR imaging. Despite this, they found that this did not directly affect future short-term participation in the National Football League.…”
Section: Discussionmentioning
confidence: 81%
“…15,18,20 In the National Football League (NFL), the impact of predraft injuries and surgical procedures, including anterior cruciate ligament reconstruction, rotator cuff tears, and shoulder labral tears, has been reported extensively from the medical records of the treating physicians; the findings portend unfavorable career prognoses for those with a musculoskeletal injury history, including a lower likelihood of a successful draft and a greater likelihood of decreased performance. 1,2,9,13,17…”
mentioning
confidence: 99%